Situación actual de corrupción colombiana y su afectación a nivel internacional para la inversión (2012)
In recent years Colombia has been experiencing social, economic and political controversial situations, which are affecting economically this country, also these internal problems cause that Colombia has a badly positioned on the outside, situations such as: the corruption of our leaders, drug trafficking, trafficking in influences, terrorism, etc.. Are the causes that Colombia does not show as an attractive country to invest. In recent years Colombia has lived corruption situations which ones have allowed to doubt about the good intentions of many Colombian congressmen who were stripped of his office and handed over to the authorities concerned, taking into now more than 15 congressmen paying penalties in national prisons for political offenses such as embezzlement, bribery, malfeasance, misappropriation, abuse of public office, para-politics, among others.